2012
DOI: 10.1104/pp.112.202192
|View full text |Cite
|
Sign up to set email alerts
|

LONO1Encoding a Nucleoporin Is Required for Embryogenesis and Seed Viability in Arabidopsis      

Abstract: Early embryogenesis in Arabidopsis (Arabidopsis thaliana) is distinguished by a predictable pattern of cell divisions and is a good system for investigating mechanisms of developmental pattern formation. Here, we identified a gene called LONO1 (LNO1) in Arabidopsis in which mutations can abolish the first asymmetrical cell division of the zygote, alter planes and number of cell divisions in early embryogenesis, and eventually arrest embryo development. LNO1 is highly expressed in anthers of flower buds, stigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 81 publications
(100 reference statements)
1
25
0
1
Order By: Relevance
“…Plant Gle1 is involved in nuclear mRNA export by interacting with LOS4 to stimulate LOS4 ATPase/RNA helicase activity. Functions of Gle1 are essential for embryogenesis (Braud et al, 2012) and critical for the postembryonic growth of plants (Figure 1), which is reminiscent of essential Gle1 functions in both yeast and mammals (Murphy and Wente, 1996;Nousiainen et al, 2008). Montpetit et al (2011) recently proposed the molecular mechanism of Dbp5/Gle1-driven mRNA export in yeast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant Gle1 is involved in nuclear mRNA export by interacting with LOS4 to stimulate LOS4 ATPase/RNA helicase activity. Functions of Gle1 are essential for embryogenesis (Braud et al, 2012) and critical for the postembryonic growth of plants (Figure 1), which is reminiscent of essential Gle1 functions in both yeast and mammals (Murphy and Wente, 1996;Nousiainen et al, 2008). Montpetit et al (2011) recently proposed the molecular mechanism of Dbp5/Gle1-driven mRNA export in yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Gle1 is also found in the cytosol and plays a role in translation initiation and termination in Dbp5-independent and -dependent manners, respectively (Bolger et al, 2008;Kutay and Panse, 2008). In plants, the cellular functions of Gle1 are unknown except that the T-DNA insertion mutation of Arabidopsis thaliana Gle1 causes an embryo lethal phenotype (Braud et al, 2012). Here, we reveal the cellular function of Gle1 in plants in relation to LOS4 and InsP 6 and show that modified Gle1 with increased InsP 6 sensitivity complements the ipk1 low-phytate mutation.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are vital and mutations in AtGLE1 and LNO1 result in non-viable seeds in Arabidopsis. 24 Both los4-1 and los4-2 mutants show abnormal mRNA localization, but are viable, 31 and this could be due to that both of los4-1 and los4-2 are missense mutations instead of null alleles. Therefore, it is tempting to speculate that a null allele of the los4 mutant might have a similar seed abortion phenotype as lno1 and Atgle1.…”
Section: Discussionmentioning
confidence: 99%
“…30 As in the Arabidopsis lno1 mutant, mutations in AtGLE1 also result in embryo abortion. 24 We have shown that LNO1 specifically interacts with LOW EXPRESSION OF OSMOTICALLY RESPONSIVE GENES 4 (LOS4) in a yeast two-hybrid assay. LOS4 encodes a DEAD box RNA helicase/ATPase in Arabidopsis.…”
mentioning
confidence: 99%
See 1 more Smart Citation